Program GAES (Grow And Eat Smart): Peningkatan Kewaspadaan terhadap Beban Gizi Ganda pada Anak dan Remaja di LKSA (Lembaga Kesejahteraan Sosial Anak) - Aloysia Ispriantari; Musthika Wida Mashitah; Indari Indari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
One of the vulnerable groups facing the double burden of malnutrition is children living in Child Social Welfare Institutions (LKSA), such as the LKSA Christian Orphanage Foundation in Malang City. This LKSA holds a C-level accreditation status, indicating limited resources and inadequate facilities to support children's well-being. Preliminary research revealed that many children are unaware of their nutritional status and have not received regular health check-ups or nutritional monitoring. To address this issue, the GAES Program (Grow And Eat Smart) was developed with the goal of increasing awareness about the double burden of malnutrition and enhancing education on the importance of regular nutritional status monitoring for children. The GAES Program consists of three main activities: distribution of nutritional measurement tools (scales and height measuring instruments), education on the importance of routine nutritional monitoring, and training in anthropometric screening techniques. The program's results showed that out of the 13 participating children, 7 children (54%) were identified as undernourished, while 6 children (46%) had good nutritional status. In addition, all participants successfully understood the educational material delivered during the sessions and were able to perform anthropometric measurements independently as an initial step in screening their nutritional status. Through this initiative, it is expected that both the children and the LKSA management will become more aware of the importance of regular nutritional monitoring and take early preventive actions. Furthermore, health professionals and local health centers (Puskesmas) are encouraged to provide continuous support and interventions at the LKSA to improve the nutritional status of children and adolescents. Such efforts are essential to prevent the long-term health impacts of the double burden of malnutrition and to ensure a healthier future for children living in social welfare institutions.